2012
DOI: 10.1177/1098612x12464873
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between auricular and rectal measurements of body temperature in healthy cats

Abstract: Measurement of body temperature is a routine part of the clinical assessment of a patient. However, this procedure may be time-consuming and stressful to most animals because the standard site of temperature acquisition remains the rectal mucosa. Although an increasing number of clinicians have been using auricular temperature to estimate core body temperature, evidence is still lacking regarding agreement between these two methods in cats. In this investigation, we evaluated the agreement between temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 13 publications
3
49
0
4
Order By: Relevance
“…No study in veterinary medicine has examined the level of experience affecting assessment of body temperature. Auricular temperature measurement was performed with strong agreement by 2 investigators in dogs and cats, both were reported to be experienced with the device.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No study in veterinary medicine has examined the level of experience affecting assessment of body temperature. Auricular temperature measurement was performed with strong agreement by 2 investigators in dogs and cats, both were reported to be experienced with the device.…”
Section: Discussionmentioning
confidence: 99%
“…7 Following on from developments in human medicine, noncontact noninvasive thermometers may be the future for temperature assessment in animals. Several studies have evaluated infrared auricular thermometers in dogs, 2,7,11,12,16,19 cats, 36,37 and other species 1,17,20 with various results. Veterinary use of the noncontact infrared technology at other locations than the ear has so far only been performed in monkeys, 33,38,39 guinea pigs, 34 and horses, 40 all with poor results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary medicine, axillary temperature measurement (ATM) and auricular temperature measurement have been compared with RTM in studies in dogs, cats, monkeys, deer, cattle, calves and swine but the results are conflicting (Myers and Henderson 1996, Drew 1998, Kunkle and others 2004, Greer and others 2007, Sikoski and others 2007, Garner 2011, Sousa and others 2011, Lamb and McBrearty 2013, Sousa and others 2013, Goic and others 2014, Gomart and others 2014, Smith and others 2015). In a previous study performed at the same institution, axillary temperature (AT) appeared to be correlated with and was less stressful than RT recording in dogs (Gomart and others 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when auricular thermometry was investigated in cats, the limits of agreement between ear and rectal measurements were much narrower and ranged from –0.5°C to 0.4°C, with the mean (sd) difference between the two sites being –0.06 (0.23)°C (Sousa and others 2013). This seemed acceptable in a clinical setting because the potential error in temperature readings remained below 0.5°C.…”
mentioning
confidence: 96%